2010
DOI: 10.1160/th10-02-0091
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation in rheumatoid arthritis: Dependence on plasma factor composition

Abstract: Summary Background Growing evidence indicates that rheumatoid arthritis (RA) is associated with an increased risk for thromboembolic cardiovascular events. Objectives We investigated thrombin generation profiles in RA patients and their dependence on plasma factor/inhibitor composition. Patients/Methods Plasma factor (F) compositions (FII, V, VII, VIII, IX, X), antithrombin and free tissue factor pathway inhibitor (TFPI) from 46 consecutive RA patients with no cardiovascular events (39F, 7M, aged 57 [rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 25 publications
3
34
2
Order By: Relevance
“…To determine which factor(s) were responsible for differences between cases and controls, we used a previously described procedure39, 40 in which each of the individuals in the mortality group had one of the factor levels sequentially adjusted to the mean of the control group and the reaction rerun with a 5 pmol/L TF stimulus and in silico thrombin outputs recalculated. This process was repeated for each factor (and expanded to multiple factors simultaneously).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine which factor(s) were responsible for differences between cases and controls, we used a previously described procedure39, 40 in which each of the individuals in the mortality group had one of the factor levels sequentially adjusted to the mean of the control group and the reaction rerun with a 5 pmol/L TF stimulus and in silico thrombin outputs recalculated. This process was repeated for each factor (and expanded to multiple factors simultaneously).…”
Section: Methodsmentioning
confidence: 99%
“…We believe that the sum of developmental, environmental, genetic, nutritional, and pharmacological influences are reflected in the protein levels at any given time that specifically alter the synthesis and/or presentation of the proteins and active enzymes. We have described changes in thrombin generation and related these changes to plasma coagulation factor composition in the following groups: genetic bleeding tendencies30, 31, 32, 33 and clotting tendencies34, 35; women undergoing in vitro fertilization36; chronic obstructive pulmonary disease37; stroke38; rheumatoid arthritis39; and cardiovascular disease 40. In all cases, thrombin generation was more pronounced in individuals with procoagulant vs bleeding tendencies 30, 31, 32.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[74][75][76] In general, the following fi ndings contribute to increase the risk of thromboembolism: lower mobility consequent to joint lesions; hospitalizations with prolonged bed confi nement; more advanced age of most arthritic patients; compression of the venous system adjacent to a joint with huge joint effusion; and obesity. 74 Patients with RA have changes in the coagulation parameters and in the fi brinolytic system, 77 the most common fi ndings being as follows: increased platelet count; increased platelet activation markers; and increased thrombin markers, such as thrombin-antithrombin complexes and prothrombin fragments. The increase in pro-infl ammatory cytokines in RA is associated with high levels of fi brinogen, von Willebrand factor, and D-dimer.…”
Section: Venous Thrombosis and Pulmonary Embolismmentioning
confidence: 99%
“…The increase in pro-infl ammatory cytokines in RA is associated with high levels of fi brinogen, von Willebrand factor, and D-dimer. 77,78 Although the studies on the prevalence of DVT and PTE in RA have shown discordant results, an important study has reported that RA is a risk factor for DVT and PTE. 75,79,80 That study has assessed the incidence of DVT and PTE in patients with RA hospitalized in the United States from 1979 to 2005.…”
Section: Venous Thrombosis and Pulmonary Embolismmentioning
confidence: 99%